2016
DOI: 10.1038/ncomms13199
|View full text |Cite
|
Sign up to set email alerts
|

Permanent ferroelectric retention of BiFeO3 mesocrystal

Abstract: Non-volatile electronic devices based on magnetoelectric multiferroics have triggered new possibilities of outperforming conventional devices for applications. However, ferroelectric reliability issues, such as imprint, retention and fatigue, must be solved before the realization of practical devices. In this study, everlasting ferroelectric retention in the heteroepitaxially constrained multiferroic mesocrystal is reported, suggesting a new approach to overcome the failure of ferroelectric retention. Studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…2h), suggesting robust stability. The super-long retention time is comparable to the longest retention time of classical perovskite-type oxide ferroelectrics electrically poled by a scanning probe 50,51 .…”
Section: Resultsmentioning
confidence: 78%
“…2h), suggesting robust stability. The super-long retention time is comparable to the longest retention time of classical perovskite-type oxide ferroelectrics electrically poled by a scanning probe 50,51 .…”
Section: Resultsmentioning
confidence: 78%
“…This work BFO/LNO mixed region, Diameter 140 nm [31] BFO/LNO mixed region, Diameter 95 nm [31] BFO/LNO T matrix, Diameter 95 nm [31] BFO/LNO unstrained, Diameter 80 nm [31] BFO/SRO R matrix, Diameter 225 nm [29] All the figure legends are for decay trend (e.g., 79.4 nm at t = 0 h and 79.1 nm at t = 8900 h). In addition, concomitant with the switched domains, some bright needle-like structures that exhibit higher piezoresponse than the matrix are formed around.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that the in-plane (IP) periodic elastic potentials at the R/T mixed boundaries act as pining centres to maintain domain stability. In another work, (111)-oriented BFO mesocrystals were grown within a stiff matrix of CoFe 2 O 4 31 . This matrix can mechanically clamp the BFO mesocrystals, thereby suppressing the ferroelectric relaxation process.…”
mentioning
confidence: 99%
“…Besides photovoltaics effect, bandgap of BFO nanomaterials lying in the visible-light region of the solar spectrum extends its horizons to the field of photocatalysis, especially the BFO nanostructures. Great catalytic properties of BFO nanostructures were found on different dyes such as methyl orange [ 116 , 117 ], Rhodamine B [ 118 , 119 ], and methylene blue [ 36 , 120 ]. Many factors affect the photocatalysis behavior, such as size effect, morphologies, and the addition of a proper dopant.…”
Section: Properties Of Bfomentioning
confidence: 99%